Pro-Cons upon Facebook Comments of Robert Mugabe's Speech at AU Summit 2016: Pragmatic-Stylistic Point of View - Alfiyah Rusdiyana; Slamet Setiawan (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2021)
ABSTRACT: This research aimed to describe the pro-cons figure of speech on a Facebook comment from Robert Mugabe Speech at AU 2016. The description of this research is using pragma-stylistics analysis. Utilization of figure of speech is personification, metaphor, hyperbole, litotes, metonymy, synecdoche, paradox, irony, parallelism, alliteration, allegory, meiosis, idioms, antithesis, sarcasm, epizeuxis, and climax. Data were gathered from the responses from a Facebook comment of the people to the speech delivered by Robert Mugabe Speech at AU Summit 2016 Addis Ababa Ethiopia was upload or share by A Do on December 22, 2018, at 9.41 PM. Text by text analysis is favoured in this study so that the various contextual issues can be easily construed; hence the practice and expressive means can be understood. The finding on this analysis, there are nine hundred and fifty, which pro-cons comment on Mugabeâ€™s speech at AU 2016 are figures of speech. The conclusion shows that Pro and cons Facebook comment on Mugabe speech from the netizen is to express their feeling about African leader. The language is used freely; the cons with Mugabe are a lot because they are satisfied and did not satisfied with his leader, they cannot talk indirectly because they feel intimidated with Mugabeâ€™s Power.Â